Suggestions from Geroscience for the Genetics of Age-Related Diseases - Franceschi, Claudio; Garagnani, Paolo (PLoS genetics, 2016)
[...]the authors were able to validate risk loci buried in well studied datasets. The revolution in hygiene awareness, a major contributor to the unprecedented increase of life expectancy, and the concomitant emergence of an obesogenic environment (easy access to nutrient-rich food; reduced physical activity) exemplify changes that promoted the epidemiological explosion of obesity, metabolic disorders, and eventually of major age-associated diseases. [...]subsequent generations were exposed to quite different environmental conditions and pressures during the last century, and it is easy to predict that the risk/protective effects of specific alleles changed accordingly.